Harnessing the surface structure to enable high-performance cathode materials for lithium-ion batteries - Yang, Luyi; Yang, Kai; Zheng, Jiaxin; Xu, Kang; Amine, Khalil; Pan, Feng (Chemical Society reviews, 2020)
The ever-increasing demand for high-performance batteries has been driving the fundamental understanding of the crystal/surface structural and electrochemical properties of intercalation cathode materials, among which the olivine-type, spinel, and layered lithium transition metal oxide materials have received particular attention in the past decade due to their successful commercialization. While the most current studies focus on the macroscopic and bulk crystal structure of these materials, our previous work suggests that, as a confined region wherein charge transfer takes place, the electrochemical performances of the interfacial structures of cathode materials are largely dictated by the break in the structural symmetry from 3D (bulk) to 2D (surface), which leads to reconstructions under different chemical/electrochemical conditions. By summarizing various works in this subject and offering our perspectives, this tutorial review will reveal for the first time the correlation between the surface structure and interface reconstruction at atomic/molecular scales and their direct impact on the corresponding electrochemical performances. More importantly, by extending the knowledge obtained from these three well-studied system, we believe that the same established principles could universally apply to other cathode materials that have been the frontiers of new battery chemistries. The impact of surface structure and interface reconstruction on the electrochemical performances of lithium-ion battery cathode materials is summarized.